Sarf Ibtida’iy Assessment with Opexams Among University Students Based on Artificial Intelligence - Akhmad Yusuf Isnan Setiawan; Inayah Inayah; Muhammad Izzul Muhtar; Feri Aditia Saputra; Asma’ Na’im Jamil Abu Samra (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
This study aims to characterize Opexams and evaluate their effectiveness on the learning outcomes of shart-ibtida